2001
DOI: 10.1097/00007435-200105000-00007
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human Papillomavirus Infection in Mexican Males

Abstract: Human papillomavirus is a common sexually transmitted infection among Mexican males, and urine sample specimens cannot adequately detect the presence of this infection in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
18
2
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 14 publications
9
18
2
6
Order By: Relevance
“…Our sampling method, which involved the collection of cells from the skin of the glans penis and coronal sulcus, is a noninvasive method that enables easy sampling of male participants. The DNA yield from these penile samples, at 90.1%, falls within the range reported in other studies of HPV in men [10,15]. However, we were unable to obtain adequate DNA from most urethral and urine samples.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our sampling method, which involved the collection of cells from the skin of the glans penis and coronal sulcus, is a noninvasive method that enables easy sampling of male participants. The DNA yield from these penile samples, at 90.1%, falls within the range reported in other studies of HPV in men [10,15]. However, we were unable to obtain adequate DNA from most urethral and urine samples.…”
Section: Discussionsupporting
confidence: 79%
“…A prewetted urethral swab was inserted 1 cm into the urethral meatus and rotated 360Њ, consistent with methods described in previous studies of male HPV that described sampling the "distal meatus" [15,21,22]. However, a study of HPV in Mexican men published after our study was under way described a urethral sampling technique in which the swab was inserted 2 cm into the meatus; those authors reported a high yield of human DNA from the urethra [10]. Our low b-globin yield may also have been the result of inadequate laboratory techniques for DNA extraction.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations